2022
DOI: 10.3389/fdgth.2022.1010779
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of video animations as information tools for patients and the general public: A systematic review

Abstract: Background and objectivesVideo animations are used increasingly as patient information tools; however, we do not know their value compared to other formats of delivery, such as printed materials, verbal consultations or static images.MethodsThis review compares the effectiveness of video animations as information tools vs. other formats of delivery on patient knowledge, attitudes and cognitions, and behaviours. Included studies had the following features: controlled design with random or quasi-random allocatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 52 publications
1
13
0
Order By: Relevance
“…For example, in non-healthcare settings the relative benefits of animations over static pictures were greater when procedural knowledge was being taught [ 8 ] and when a more realistic animation style was being used. When used with patients, animations have shown a similar pattern to those reported in this review: mostly beneficial effects on knowledge, and mixed findings (and much less evidence) on attitudes, cognitions and behaviour [ 7 ].…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…For example, in non-healthcare settings the relative benefits of animations over static pictures were greater when procedural knowledge was being taught [ 8 ] and when a more realistic animation style was being used. When used with patients, animations have shown a similar pattern to those reported in this review: mostly beneficial effects on knowledge, and mixed findings (and much less evidence) on attitudes, cognitions and behaviour [ 7 ].…”
Section: Discussionmentioning
confidence: 72%
“…Animations were not always shown to be beneficial in the included studies, but there are several results that indicate promising effects: these need replication, particularly in bigger, more definitive trials. As in patient settings [ 7 ], this review found a lack of research for the effects on behaviour, and this warrants further investigation. Furthermore, it would be useful for studies to assess the relative effects of ‘representational’ and ‘decorative’ animation styles, which was found to be important in non-healthcare education [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moe-Byrne et al have suggested after the evidence was evaluated in 2022 that the use of animations is a more effective means to deliver education/information compared with traditional paper-based information sheets, although the authors commented that the evidence base was highly variable and mostly based on small trials [ 10 ]. However, there are some large standalone studies—one such study comes from the USA, where 1194 cancer patients and survivors took part in a four-arm experiment to assess the effects of EAs compared with text-only brochures, brochures with visuals and the materials that were currently in use by the National Institute for Health (NIH) [ 11 ].…”
Section: Introductionmentioning
confidence: 99%